2000
DOI: 10.1148/radiology.216.1.r00jl19117
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculoma Evaluated by Means of FDG PET: Findings in 10 Cases

Abstract: Pulmonary tuberculoma commonly causes an increase in FDG uptake. These results suggest that in geographic regions with a high prevalence of granulomatous lesions, positive FDG PET results should be interpreted with caution in differentiating benign from malignant pulmonary abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
189
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(203 citation statements)
references
References 17 publications
5
189
1
6
Order By: Relevance
“…However, FDG-PET has given false-negative results for well-differentiated pulmonary adenocarcinoma (Higashi et al, 1998;Cheran et al, 2004), or small volumes of metabolically active tumor (Satoh et al, 2011), and false-positive results for inflammatory nodules (Goo et al, 2000;Nomori et al, 2004). In addition, FDG-PET is not widely available because of its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…However, FDG-PET has given false-negative results for well-differentiated pulmonary adenocarcinoma (Higashi et al, 1998;Cheran et al, 2004), or small volumes of metabolically active tumor (Satoh et al, 2011), and false-positive results for inflammatory nodules (Goo et al, 2000;Nomori et al, 2004). In addition, FDG-PET is not widely available because of its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that the highest [5][6][7]. However, some benign inflammatory lesions could show F-18 FDG accumulation yielding false positive findings [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…tense FDG uptake (1). However, it is rare that FDG-PET scans revealed partial intense FDG uptake in the nodule.…”
Section: P I C T U R Ementioning
confidence: 99%